Isti‘mār Al-Arḍ: The Concept of Prosperity for the Earth from Qur‘ānic Perspective - Yunus, Badruzzaman M. (International Journal of Psychosocial Rehabilitation, 2020)
This article tries to uncover the concept of prosperity of the earth which begins with verse 61 of Sūrat Hūd, then continues by connecting it with other verses in the Qur‟ān and the Ḥadīth. The concept contains a message or a strong signal, even a command that humans can prosper the earth as a form of environmental preservation by maintaining the balance of nature. The method used is the thematic tafsīr or al-tafsīr al-mawḍū’ī which sees the verses of the Qur‟ān as a unified meaning and confirms that in the Qur‟ān there are no verses that contradict the others. This article found that God created humans from the earth and God told them to manage and prosper it while banning it from spoiling it. The earth and all its contents are intended for the survival and comfort of human life. This article concludes that the damage that has ever happened on earth is a result of human activity itself that does not act as God commands.